PENERAPAN MODEL PEMBELAJARAN ADVANCE ORGANIZER UNTUK MENINGKATKAN PENGUASAAN KONSEP FISIKA SISWA SMA - Fitri Kusuma Ningrum; Muhammad Nasir; Muhammad Rahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
This research aimed to determine the improve in mastery of students' physics concepts through the application of an advanced organizer model on material momentum and impulses. The research method used was quasy experiment with pretest posttest control group design. The research population is all students of class X MIPA SMAN 1 Rumbio Jaya which is a sample of research with class X MIPA 1 as an experimental class totaling 23 students and class X MIPA 2 as a control class of 24 students. The research instrument used the concept mastery test questions. Data were analyzed descriptively by looking at absorption, learning effectiveness and the results of students' concept mastery scores and analyzed inferentially using the T-test. Descriptive analysis results obtained an average absorption of experimental class students by 81.61% with the effectiveness of learning categorized effectively. Furthermore, for the mastery of the concept of each experimental class indicator on the first and second indicators obtained very good categories, the third indicator obtained the medium category and the fourth indicator with a low category. The results of inferential analysis obtained a significant increase in the mastery of student concepts in the class applying the Advance Organizer learning model to the classroom with conventional learning. Based on the results of the research, the advanced organizer learning model can improve students' mastery of the concepts in the material momentum and impulses of class X SMAN 1 Rumbio Jaya.